2022
DOI: 10.1101/2022.03.01.22271660
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Examining the Impact of ICU Population Interaction Structure on Modeled Colonization Dynamics ofStaphylococcus aureus

Abstract: BackgroundComplex transmission models of healthcare-associated infections provide insight for hospital epidemiology and infection control efforts; however, many are difficult to implement and come at high computational costs. Structuring more simplified models to incorporate the heterogeneity of the intensive care unit (ICU) patient-provider interactions, we explore how methicillin-resistant Staphylococcus aureus (MRSA) dynamics and acquisitions may be better represented and approximated.MethodsUsing a stochas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
(73 reference statements)
0
3
0
Order By: Relevance
“…We adapted stochastic compartmental models published in 2019 4 and 2017 5 of transmission of MRSA through an ICU. Our model included compartments for patient colonization status and the presence or absence of contamination on the hands or clothing of health care workers (HCWs).…”
Section: Mrsa Transmission Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…We adapted stochastic compartmental models published in 2019 4 and 2017 5 of transmission of MRSA through an ICU. Our model included compartments for patient colonization status and the presence or absence of contamination on the hands or clothing of health care workers (HCWs).…”
Section: Mrsa Transmission Modelmentioning
confidence: 99%
“…Because an ICU is a highly structured population, this model relaxed the random mixing assumption used in many compartmental models, instead subdividing the patient population such that each patient was cared for by a single nurse who exclusively cared for 3 patients. While this is a simplification of the structure of an ICU, a 2019 study 4 found that this assumption was associated with more conservative outcomes compared with random mixing. The intensivist was assumed to treat all patients (Figure 2).…”
Section: Mrsa Transmission Modelmentioning
confidence: 99%
See 1 more Smart Citation